Continuous Flow Injection Analysis for The Photometric Determination of Metformin Drug Via The Release of Copper(II) ion from Charged Gel Bead Crystal - Shakir, Issam; Al-Awadi, Nagam (Iraqi Journal of Science, 2023)
A newly developed analytical method characterized by its speed and sensitivity for the determination of metformin-HCl via the formation of complex for metformin-HCl-OH–copper(II) ion from the gel bead system by continuous flow injection analysis. The method is based on the imbedded copper(II) ion in the gel bead structure can be used in the reaction for the formation of red –magneta colour complex(λmax. =530nm) formed by direct reaction of the drug with the released copper (II) ion from the gel bead in alkaline medium. Linear dynamic range for the absorbance versus metformin concentration was 0.001-1 mmol.L-1 while C.O.D was (r2% =95.33%) . The L.O.Q was 0.868mmol.L-1.L.O.D (S/N=3)=0.5μmol.L-1 from the step wise dilution for the minimum concentration of lowest concentration in the linear dynamic ranged of the calibration graph with R.S.D% lower than 0.5% for 0.01 mmol.L -1( n=8) concentration of metformin- HCl, throughput 30 sample.hr-1. The method was applied successfully for the determination of metformin in three pharmaceutical drugs. A comparison was made between the newly developed method of analysis with the classical method(Uv-spectrophotometry at wave length = 241nm) of analysis using the standard addition method via the use of paired t-test. It shows that there was no significant difference at α= 0.05 (95% confidence) between the two methods. Therefore the newly developed method(using the Metformin- OH- - Cu(II) entrapped inside gel bead) can be adopted as an alternative method for the analysis of metformin.